2002
DOI: 10.1152/japplphysiol.00394.2002
|View full text |Cite
|
Sign up to set email alerts
|

Early postexercise muscle glycogen recovery is enhanced with a carbohydrate-protein supplement

Abstract: In the present study, we tested the hypothesis that a carbohydrate-protein (CHO-Pro) supplement would be more effective in the replenishment of muscle glycogen after exercise compared with a carbohydrate supplement of equal carbohydrate content (LCHO) or caloric equivalency (HCHO). After 2.5 +/- 0.1 h of intense cycling to deplete the muscle glycogen stores, subjects (n = 7) received, using a rank-ordered design, a CHO-Pro (80 g CHO, 28 g Pro, 6 g fat), LCHO (80 g CHO, 6 g fat), or HCHO (108 g CHO, 6 g fat) su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
201
2
11

Year Published

2004
2004
2014
2014

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 269 publications
(225 citation statements)
references
References 29 publications
11
201
2
11
Order By: Relevance
“…In another study including only NT women, 7 a marked reduction in BP was observed after acute dynamic exercise in middle-aged and elderly women but not in young women. Other studies 8,9 have shown greater BP reductions in persons aged 41-60 years compared with older and younger individuals.Ambulatory arterial blood pressure monitoring (ABPM) has been extensively used to obtain more detailed information about BP …”
mentioning
confidence: 83%
“…In another study including only NT women, 7 a marked reduction in BP was observed after acute dynamic exercise in middle-aged and elderly women but not in young women. Other studies 8,9 have shown greater BP reductions in persons aged 41-60 years compared with older and younger individuals.Ambulatory arterial blood pressure monitoring (ABPM) has been extensively used to obtain more detailed information about BP …”
mentioning
confidence: 83%
“…Ivy et al 30 discussed some methodological variances that could explain these inconsistencies, including differences in carbohydrate and protein concentrations in supplements, supplement administration protocols, time period of recovery measurements, and applied exercise protocols. Since this is the first study to investigate, in practice, the effect of CHO supplementation along with pea protein by means of the LRT, comparisons with other findings are limited.…”
Section: Discussionmentioning
confidence: 99%
“…For example, as discussed by Burke et al (2004) and Ivy and colleagues (Zawadzki et al, 1992;Ivy, 2001;Ivy et al, 2002), the addition of small amounts of protein to carbohydrate ingested after exercise augments the plasma insulin response, which has the potential to alter metabolism. However, at present there is insufficient theoretical rationale or data to recommend inclusion of protein in solutions ingested during exercise.…”
Section: Intake Of Other Fuels During Exercisementioning
confidence: 99%